Pengaruh Leverage, Sales Growth, Kompensasi Rugi Fiskal dan Koneksi Politik terhadap Penghindaran Pajak (Studi Empiris Pada Perusahaan Manufaktur Yang Terdaftar di BEI Tahun 2017-2022) - Sholihah, El Fira Mar’atus; Rahmiati, Alfa (Politeknik Ganesha Medan, 2024)
This study aims to examine (1) the effect of leverage on tax avoidance (2) the effect of sales growth on tax avoidance (3) the effect of fiscal loss compensation on tax avoidance (4) the effect of political connections on tax avoidance in manufacturing companies listed on the Indonesia Stock Exchange in 2017 – 2022. The research sample was determined based on the purposive sampling method. The data analysis technique uses multiple linear regression analysis with tax avoidance as the dependent variable and leverage, sales growth, fiscal loss compensation and political connections as independent variables. Data processing using SPSS version 17.0. The results of this study indicate that (1) leverage has an effect on tax avoidance (2) sales growth has no effect on tax avoidance (3) fiscal loss compensation has an effect on tax avoidance (4) political connections does not affect tax avoidance (tax avoidance).